Constituents of Music and Visual-Art Related Pleasure – A Critical Integrative Literature Review - Tiihonen, Marianne; Brattico, Elvira; Maksimainen, Johanna; Wikgren, Jan; Saarikallio, Suvi (Frontiers in Psychology, 2017)
The present literature review investigated how pleasure induced by music and visual-art has been conceptually understood in empirical research over the past twenty years. After an initial selection of abstracts from seven databases (keywords: pleasure, reward, enjoyment, and hedonic), twenty music and eleven visual-art papers were systematically compared. The following questions were addressed: 1. What is the role of the keyword in the research question? 2. Is pleasure considered a result of variation in the perceiver’s internal or external attributes? 3. What are the most commonly employed methods and main variables in empirical settings? Based on these questions, our critical integrative analysis aimed to identify which themes and processes emerged as key features for conceptualizing art-induced pleasure. The results demonstrated great variance in how pleasure has been approached: In the music studies pleasure was often a clear object of investigation, whereas in the visual-art studies the term was often embedded into the context of an aesthetic experience, or used otherwise in a descriptive, indirect sense. Music studies often targeted different emotions, their intensity or anhedonia. Biographical & background variables and personality traits of the perceiver were often measured. Next to behavioural methods, a common method was brain imaging which often targeted the reward circuitry of the brain in response to music. Visual-art pleasure was also frequently addressed using brain imaging methods, but the research focused on sensory cortices rather than the reward circuit alone. Compared with music research, visual-art research investigated more frequently pleasure in relation to conscious, cognitive processing, where the variations of stimulus features and the changing of viewing modes were regarded as explanatory factors of the derived experience. Despite valence being frequently applied in both domains, we conclude, that in empirical music research pleasure seems to be part of core affect and hedonic tone modulated by stable personality variables, whereas in visual-art research pleasure is a result of the so called conceptual act depending on a chosen strategy to approach art. We encourage an integration of music and visual-art into to a multi-modal framework to promote a more versatile understanding of pleasure in response to aesthetic artefacts.